Enhanced Bacterial Tumor Delivery by Modulating the EPR Effect and Therapeutic Potential of Lactobacillus casei. Issue 10 (16th July 2014) - Fang, Jun; Liao, Long; Yin, Hongzhuan; Nakamura, Hideaki; Shin, Takashi; Maeda, Hiroshi
<x xml:space="preserve">Abstract</x> Bacteria of micrometer size could accumulate in tumor based on enhanced permeability and retention (EPR) effect. We report here Lactobacillus casei (L. casei), a nonpathogenic facultatively anaerobic bacterium, preferentially accumulated in tumor tissues after intravenously (i.v.) injection; at 24 h, live bacteria were found more in the tumor, whereas the bacteria in normal tissues including the liver and spleen were cleared rapidly. The tumor‐selective accumulation and growth of L. casei is probably due to the EPR effect and the hypoxic tumor environment. Moreover, the bacterial tumor delivery was significantly increased by a nitric oxide (NO) donor nitroglycerin (NG, 10–70 times) and an angiotensin II converting enzyme inhibitor, enalapril (6–18 times). Consequently significant suppression of tumor growth was found in a colon cancer C26 model, and more remarkable antitumor effect was achieved when L. casei was combined with NG, probably by modulating the host nonspecific immune responses; tumor necrosis factor‐α significantly increased in tumor after the treatment, as well as NO synthase activity and myleoperoxidase activity. These findings suggest the potential of L. casei as a candidate for targeted bacterial antitumor therapy, especially in combine with NG or other vascular mediators. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3235–3243, 2014